Proposta de retrofitting em sistema para abastecimento de gás natural veicular - Gemelli, Valdir Junior (2015)
This work presents a proposal on modernization of automated monitoring system of vehicular natural gas compressor, by changing the control hardware, programmable logic controller, and the program that performs the monitoring of variables inherent in the process, with the intuited to improve the operation and safety of all involved in compressor operation, while maintaining the same mechanical properties of the original compressor project, which has as working site, gas stations.